Identification and Host Range Tests of Colletotrichum sp. Associated with the Manalagi Mango Cultivar - Azizah Ridha Ulilalbab; Aura Dhamira; Miftahul Ajri; Danar Wicaksono; Mofit Eko Poerwanto; Seto Agung Kuncoro (AGROISTA : Jurnal Agroteknologi, 2026)
Anthracnose is a significant disease in mango production and other tropical fruits, often causing major yield reductions. The disease is caused by the fungal pathogen Colletotrichum sp. could infect many fruits commodities included mango. This study aims to identify morphological Colletotrichum spp. associated in Manalagi Mango and its host-range test among the fruits. Two isolates (MM1 and MM2) were obtained from symptomatic mango fruits and characterized based on macroscopic and microscopic morphological features. Both isolates exhibited rapid mycelial growth and cylindrical conidia, consistent with characteristics of the Colletotrichum species. Host-range tests were performed on citrus, chayote, tomato, and cayenne pepper. MM1 showed limited host range, while MM2 infected all tested hosts with higher aggressiveness, especially on tomato and cayenne pepper. The results confirmed the wide host adaptability of Colletotrichum spp. and their potential for host-range among fruit commodities. Accurate identification and host-range assessment are critical for effective anthracnose disease management, and future studies should incorporate molecular tools for precise species delineation